(untitled) (REMUNOM, 2026)
This article investigates the difficulties faced by students in Youth and Adult Education (EJA) in text production and proposes didactic alternatives aimed at improving the teaching of writing in this educational modality. The study was carried out at Escola Estadual de Ensino Médio Maria Madalena Santana de Lima, located in Manaus (AM), with the objective of identifying the main barriers in writing and developing a didactic proposal capable of enhancing the development of textual competences. Using a qualitative approach and instruments such as questionnaires and didactic activities, it was found that the lack of mastery of the stages of the writing process and linguistic insecurity are central challenges. The proposal developed demonstrated effectiveness in strengthening students’ text production skills. The study reinforces the need for contextualized methodologies that respect the profile of EJA students and promote meaningful learning.